Projeto executivo assistido pela modelagem BIM como instrumento de apoio ao processo construtivo - Marques, Fernando Henrique Barbosa (2014)
This paper presents a reflection on the executive project as a result of the design process. The main objective is to propose guidelines for the executive project in order to minimize the differences between the project and the work through BIM platform. The proposed screening method is divided into two steps. The first was done a survey on construction sites of buildings multipavimentos to identify problems arising from the project and highlight the importance of the research context. The second seeks to identify the benefits of BIM platform with reflection in the work. The results obtained from the studies we have that: BIM platform has numerous advantages to the design process when applied correctly and mastery of their tools compared to two- dimensional process without parameterization. Even with all these advantages, the barriers to deploying this platform still will lack time to translate them. It might also infer that the need of the executive project is the internal customers - builders - not the contractor (finished project). After the discussion of all the data, it drew up guidelines for the preparation of the executive project, meeting the needs of agents who will use this project and using, for the most part, the BIM platform.